Utilization of Artificial Intelligence to Improve Students' Understanding through ChatGPT - Rozi, Fathor; Munif, Muhammad; Widad, Soviatul (ISLAMIKA, 2025)
With the advancement of technology in the era of revolution 5.0, effective education requires the right approach to maintain student engagement and prevent boredom in the teaching and learning process. This study aims to determine students' understanding of the subject matter through a more interactive and relevant approach, namely by utilizing ChatGPT. This study uses a qualitative descriptive approach with a case study type. The population involved in this study were students of class IX C of SMP Negeri 2 Pakuniran located in Glagah village. To collect data, this study used relevant instruments, namely observation and interviews. The results of the study show that ChatGPT as a learning aid can significantly improve student understanding, proven to be able to provide in-depth explanations and show increased motivation and learning activity. Students show high enthusiasm and curiosity in interacting with ChatGPT. They feel comfortable asking questions and discussing with this AI system because it can answer questions that go beyond the subject matter, especially for material that is difficult to understand. Interaction takes place in real-time so that students get feedback and clarification quickly.